Authority and Subjugation in Writing of Medieval Wales - Kennedy, R. author. aut Link
XX, 290 p. 5 illus.
Keywords: The conquest of Wales by the medieval English throne produced a fiercely contested territory, both militarily and culturally. Wales was left fissured by frontiers of language, jurisdiction and loyalty - a reluctant meeting place of literary traditions and political cultures. But the profound consequences of this first colonial adventure on the development of medieval English culture have been disregarded. In setting English figurations of Wales against the contrasted representations of the Welsh language tradition, this volume seeks to reverse this neglect, insisting on the crucial importance of the English experience in Wales for any understanding of the literary cultures of medieval England and medieval Britain.